Implementasi Konsep Green Entrepreneurship pada UMKM Craftonesia Kota Semarang - Tri Kusuma Wati; Khasan Setiaji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the motivation, implementation, barriers, and impacts of the green entrepreneurship concept at Craftonesia SME in Semarang City. This research employed a qualitative approach with a descriptive case study method. Data were collected through observation, in-depth interviews, and documentation involving the business owner, employees, consumers, and surrounding community members selected through purposive sampling. Data validity was tested using source triangulation and method triangulation, while data analysis followed the Miles and Huberman model encompassing data reduction, data display, and conclusion drawing. The results show that the owner's motivation was formed by five interrelated factors: environmental concern (green values), passion for crafts, positive market response (identifying gap in the market), desire for independence (being their own boss), and the need for additional income (making a living). The implementation of green entrepreneurship encompasses two main aspects: vision and mission, and production processes, including the use of waste paper as raw material, manual production with minimal pollution, natural dyes, food-grade coating, product variation, and zero waste management. Barriers encountered include limited skilled human resources, longer production time, low consumer awareness, and limited access to information on green business certification. The impacts of implementation align with the Triple Bottom Line framework, covering environmental waste reduction, community empowerment, and expanded market access through green industry exhibitions. This study concludes that micro-scale enterprises can consistently implement green entrepreneurship as a holistic and sustainable business approach.